Clinical Evaluation of Resilient Denture Liners Part 2: Candida Count and Speciation - Mary E. Brosky, DMD,1 Igor J. Pesun, DMD, MS, FACP,2 Brad Morrison, BS,3 (Journal of Prosthodontics, 2003)
The purpose of this study was to count and to speciate Candida isolated from 2 resilient denture liners, Molloplast-B and MPDS-SL.